Service-Learning Integration as Pedagogical Strategy for Enhancing Higher Education Students’ Global Citizenship Competencies - Allan Militante; Bernard Ferrer; Bien Añonuevo; Rudy Bhonne De Lara; Ernesto Bastida; Justine Joy Sabanal (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The main purpose of the study was to examine the extent of service-learning integration and the enhancement of global citizenship competencies. Methodology: Descriptive-correlational research design was employed in this study. Four hundred six (406) respondents from the different institutes of Kolehiyo ng Lungsod ng Dasmarinas, a locally funded higher education institution, were surveyed. Pearson product-moment correlation and stepwise multiple linear regression analysis were used to analyze the collected data. Main Findings: Results revealed that HEI teachers integrated service-learning approach into instructional materials designing and development, course expectations and learning standards, assessment tools and procedures, classroom management and learning environments, and lesson planning and teaching strategies to a great extent. Direct learning and research-based activities were the dominant service-learning types used for the HEI curricula. Furthermore, the global citizenship competencies indicated a significant relationship with and were influenced by the components of service-learning. Novelty/Originality of this study: This research provides a theoretical perspective about how service-learning approach influences the acquisition of global citizenship competencies among students, making them more ready and eligible for thriving in the demands of the future.